2005
DOI: 10.2174/1389557053544056
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Chemistry and Properties of 1,2,4-Thiadiazoles

Abstract: 1,2,4-Thiadiazole is a distinctive class of small heterocyclic thiol trapping agents that serve as an interesting pharmacophore in the design of inhibitors targeting the cysteine residues of proteins. X-Ray crystal structures of enzyme-inhibitor complex indicate that the cysteine thiol reacts with the N-S bond of the thiadiazole moiety to form a disulfide bond resulting in the inactivation of the enzymes. This review addresses the medicinal chemistry and various properties of 1,2,4-thiadiazoles in their potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The imidazothiadiazole 324 can exist in two likely (i.e., low-energy) tautomeric forms, the N7-H tautomer 324 and the N1-H tautomer 324a, which can interconvert via a 1,3-prototropic shift. Calculations [135] indicated that 324 has a relative energy 12.9 kcal mol À1 below that of 324a. NMR spectroscopy showed that the low-energy tautomer 324 is also present in DMSO-d 6 solution.…”
Section: 24-thiadiazolidinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The imidazothiadiazole 324 can exist in two likely (i.e., low-energy) tautomeric forms, the N7-H tautomer 324 and the N1-H tautomer 324a, which can interconvert via a 1,3-prototropic shift. Calculations [135] indicated that 324 has a relative energy 12.9 kcal mol À1 below that of 324a. NMR spectroscopy showed that the low-energy tautomer 324 is also present in DMSO-d 6 solution.…”
Section: 24-thiadiazolidinesmentioning
confidence: 99%
“…The tautomer 248, with the double bond between the a-nitrogen and the b-carbon, is the one with the lowest energy, lying 3.3 and 4.6 kcal mol À1 off the other forms, and thus is the more stable geometric structure [132]. Stable N-substituted D 4 -269 [133] and D 3 -thiadiazolines 270 [134] have been suggested as scaffolds for structure-activity investigation as N-S cysteine thiol trapping agents in enzyme systems [135]. The 5-amino-1,2,4-thiadiazolin-3-one 271, analog of cytosine, can exist in two stable tautomeric forms: lactam (oxo) 271a and lactim (enol) 271b.…”
mentioning
confidence: 99%
“…1,2 The role played by the 1,2,4-thiadiazole unit includes that of reactive warhead in irreversible enzyme inhibitors, 3 a scaffold role in more conventional enzyme inhibition 4 and binding to human muscarinic receptors. 5 More recently, 1,2,4-thiadiazoles have been optimized as inhibitors of inducible nitric oxide synthase and have shown efficacy against acute inflammation and chronic neuropathic pain, 6 have shown affinity for insect muscarinc receptor(s) and hold promise as insecticides 7 and have been demonstrated to have chemoprotective potential as a result of inhibition of aromatase and NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…Monocyclic 1,2,4-thiadiazoles have been widely claimed to be useful insecticidal, herbicidal and fungicidal agents [9]. Recently the thioltraping properties of 1,2,4-thiadiazole systems have been surveyed [10]. Although there are numerous 1,2,4-thiadiazole derivatives with interesting biological and therapeutic activities, the only commercialized 1,2,4-thiadiazole drug is the antibiotic Cefozopran [11].…”
Section: Introductionmentioning
confidence: 99%